Implementasi Peraturan Pemerintah No. 53 Tahun 2010 Tentang Disiplin Pegawai Negeri Sipil Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Tolitoli - M. Gafur Supriady (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the implementation of the policy of Government Regulation No. 53 of 2010 concerning Civil Servant Discipline, Employee Discipline Agency at the Tolitoli Regency Personnel and Human Resources Development Agency. This study used descriptive qualitative method. In determining the research informants, the writer used purposive sampling technique so that five (5) people were selected. as for data collection techniques using interviews, observation and documentation. This study uses the theory of policy implementation which consists of 4 indicators, namely communication, resources, disposition, and bureaucratic structure. The results of this study indicate that of the four indicators, only one indicator is met and three indicators are not met, namely communication is an indicator that is fulfilled and indicators of resources, disposition and bureaucratic structure are indicators that are not fulfilled.